2019
DOI: 10.1021/acssynbio.9b00033
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas12a-Mediated Gene Deletion and Regulation in Clostridium ljungdahlii and Its Application in Carbon Flux Redirection in Synthesis Gas Fermentation

Abstract: Uncovering the full potential of gas-fermenting Clostridia, attractive autotrophic bacteria capable of using synthesis gases (CO–CO2–H2) to produce a range of chemicals and fuels, for industrial applications relies on having efficient molecular tools for genetic modifications. Although the CRISPR-Cas9-mediated genome editing system has been developed in Clostridia, its use is limited owing to low GC content (approx. 30%) in these anaerobes. Therefore, the effector protein Cas12a, which recognizes T-rich instea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 33 publications
2
78
0
Order By: Relevance
“…To disrupt ljungdin production, the ljuB gene was repressed via the Cas12a‐mediated CRISPRi system developed for C. ljungdahlii . [ 32 ] Triplicate batch fermentations with the resulting mutant and the wild type C. ljungdahlii were then performed, and the growth curve as well as ethanol and acetate production were measured. The results showed that ljuB ‐repressed mutant apparently grew much faster than the wild type, as the OD 600 values were about 1.6‐, 1.3‐, and 1.1‐folds higher than those of wild type at 24, 48, and 72 h, respectively (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To disrupt ljungdin production, the ljuB gene was repressed via the Cas12a‐mediated CRISPRi system developed for C. ljungdahlii . [ 32 ] Triplicate batch fermentations with the resulting mutant and the wild type C. ljungdahlii were then performed, and the growth curve as well as ethanol and acetate production were measured. The results showed that ljuB ‐repressed mutant apparently grew much faster than the wild type, as the OD 600 values were about 1.6‐, 1.3‐, and 1.1‐folds higher than those of wild type at 24, 48, and 72 h, respectively (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, plasmid-based gene expression methods developed for Clostridium species have been shown to be functional in other acetogens. In addition, many metabolic engineering efforts have recently been made using homologous recombination (HR) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], ClosTron [ 28 , 36 , 37 , 38 , 39 ] and Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR) along with its CRISPR-associated (Cas) protein (CRISPR-Cas) system [ 32 , 40 , 41 , 42 , 43 , 44 , 45 ] to improve the production of value-added biochemicals from C1 gases.…”
Section: Development Of Genetic Manipulation Tools In Acetogensmentioning
confidence: 99%
“…43%). Cas12a recognizes AT-rich PAM sequences, “TTN”, which are more abundant than “NGG” for Cas9 in the genome [ 42 ]. One advantage of Cas12a is that its crRNA processing activity enhances the simplicity of multiplex genome editing [ 83 , 84 ].…”
Section: Development Of Genetic Manipulation Tools In Acetogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Single CRISPR/Cpf1 system plasmid can make multiple mutants in a single application (Zetsche et al, 2017;Hong et al, 2018;Zhang et al, 2018a). CRISPR/Cpf1 system has been applied in C. ljungdahlii, C. difficile, and C. beijerinckii (Hong et al, 2018;Zhang et al, 2018a;Zhao et al, 2019).…”
Section: Crispr/cas Based Clostridia Genome Engineeringmentioning
confidence: 99%